Enormous Myoma Pedunculated Through the Cervix: A Surgical Challenge - F. Futcher; P. George; N. Habib; P. Von Theobald; A. Birsan-Frances (Case Reports in Obstetrics and Gynecology)
We report the case of a 57-year-old woman who presented to the gynecological emergency department with an enormous 18 cm submucosal leiomyoma pedunculated through the cervix. She was anemic due to bleeding over the past 2 months. The aim of this study was to highlight the challenges of managing such an unusual clinical scenario. We also describe the preoperative and intraoperative methods that can be used to minimize intraoperative blood loss and improve the safety and feasibility of this kind of surgical procedure. In our case, we decided to perform a vaginal myomectomy after a tourniquet on the pedicle to reduce bleeding.